MOBILISASI ZAKAT DALAM PEWUJUDAN USAHAWAN ASNAF: SATU TINJAUAN - Mohd Balwi, Mohd Abd Wahab Fatoni (Jurnal Syariah, 2008)
Numerous efforts have been carried out to assist recipients of zakat or asnaf to break away from the vicious cycle of poverty. Several state religious authorities in Malaysia have taken the initiative to set up zakat administration bodies which are entrusted with the management of zakat collection in their respective states. Over the years, the function of zakat administration bodies have evolved from zakat collection to all aspects of zakat administration, including zakat distribution, asnaf development and poverty eradication activities. This article aims to review the concepts of zakat, asnaf and entrepreneurial development. It will also attempt to integrate these concepts with asnaf entrepreneurial creation and its development in Malaysia.